Analisis Nilai Edukatif dalam Novel Orang-orang Biasa Karya Andrea Hirata: Tinjauan Sosiologi Sastra - Nurachmana, Alifiah; Purwaka, Albertus; Supardi, Supardi; Yuliani, Yuliani (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2020)
The general objective of this research is to describe the form of educational values contained in the novel Orang-Orang Asli by Andrea Hirata (2019). The specific objectives of this study are: (1) to describe religious values (2) to describe moral values (3) how the social values contained in the novel Orang-Orang Asli by Andrea Hirata (4) describe aesthetic values (5) describe cultural values. is a descriptive qualitative research. The data used in this research are words and quotes from the novel. The data source used is the novel entitled Ordinary People. Data techniques are carried out using literature study techniques, reading techniques, and note-taking techniques. , and inference. The results of this study indicate the data 1) there are two religious values contained in the novel Orang-Orang Asli by Andrea Hirata. Data 2) there are eight moral values contained in the novel Orang-Orang Asli by Andrea Hirata. Data 3) there are four social values contained in the novel Orang-Orang Asli by Andrea Hirata. Data 4) there are two aesthetic values contained in the novel Orang-Orang Asli by Andrea Hirata. Data 5) there are two cultural values contained in the novel Orang-Orang Asli by Andrea Hirata.